PERLINDUNGAN KONSUMEN TERKAIT PEREDARAN PRODUK PEMUTIH BADAN DENGAN IZIN EDAR BPOM PALSU - Anak Agung Ngurah Naga Sena*; Dewa Gde Rudy (Jurnal Tengkhiang, 2023)
This research entitled Consumer Protection Related to the Circulation of Body Whitening Products with Fake BPOM Circulation Permits, aims to examine the legal protection for consumers when buying body whitening products with fake distribution permits with hazardous ingredients, as well as the extent of sanctions applied to rogue business actors who distribute their products with a fake BPOM distribution permit. The research method chosen by the author is the normative legal method which refers to several related regulations. This scientific journal uses primary legal materials and secondary legal materials. This research is categorized as a descriptive research. The results of this study are the circulation of body whitening products with fake BPOM distribution permits resulting in losses for consumers because they contain hazardous materials. The protection that can be given to consumer rights is contained in Article 4 of the Consumer Protection Law (hereinafter referred to as UUPK). In addition, preventive and repressive measures are also carried out by BPOM. Manufacturers of bleach products with hazardous materials and fake BPOM distribution permits may be subject to sanctions in the form of compensation as stipulated in the UUPK, administrative sanctions for business actors who do not have good ethics to be responsible for a maximum of Rp. 200,000,000.00 (two hundred million rupiah). Also subject to criminal sanctions for violating Article 204 of the Criminal Code and the criminal act of falsifying documents as regulated in Article 263 of the Criminal Code.